UJI EFEKTIVITAS WAKTU PEMANGKASAN TOPPING TERHADAP PERTUMBUHAN DAN HASIL KACANG PANJANG (Vigna sesquipedalis (L) fruhw) - Dhiar Hamdani; Sulistyo Sidik Purnomo; Rommy Andhika Laksono; Prasodjo Soedomo (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
Long beans are a food favored by Indonesian people because they have sufficient nutritional content for health. topping is a way to increase production. This study aims to determine the growth response and interaction of two varieties of Long Beans with different topping times. The research was conducted in Karawang Regency in July - August 2020. The method used was a randomized block design method with a split-plot design consisting of 2 factors. the first factor was the variety (v) with 2 levels, v1 (KP-1) and v2 (Katrina) with 4 replications. The second factor is the pruning time (p) with 3 levels, p0 (without trimming), p1 (pruning 20 days afterward), and p2 pruning 40 days afterward. If the treatment shows a significantly different effect, then proceed with the LSD 5% test. The results showed that the KP-1 variety with pruning treatment of 20 days after planting gave the highest yield with 348.20 grams per plant. Meanwhile, the highest yield of Katrina variety was in the treatment without pruning with a weight of 370.70 grams per plant.